Panggung Depan Media Sosial: Peranan Narcissistic personality dan Media Richness terhadap Online Self-Presentation Usia Emerging Adulthood - Arifah, Pauji; Mikarsa, Hera Lestari; Rahardjo, Wahyu (Jurusan Psikologi FKIP Universitas Halu Oleo, 2023)
Social media is a platform that can facilitate individuals to present themselves online. Besides being able to have a positive impact on users, self-presentation online on social media also has a negative impact, especially for adult users who are in the transition phase from adolescence to adulthood. This study aims to examine the effect of narcissistic personality and media richness on online self-presentation in adulthood. This study uses impression management theory to explain online self-presentation. There were 281 participants in this study with an age range of 18-24 years and active Instagram users. The measurement tools used are Presentation of Online Self-Scale Adult (POSSA), Narcissistic Personality Inventory (NPI-13), and Measure of Media Richness. Data analysis technique using multiple linear regression. The results of the study indicate that there is a simultaneous influence of narcissistic personality and media richness on online self-presentation. In addition, it was also partially found that narcissistic personality can affect self-presentation online, as well as media richness which is also found to affect self-presentation online.